2018
DOI: 10.3390/ma11112259
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of the CA Mortar Used in CRTS I Ballastless Slab Track under Simulated Servicing Condition

Abstract: The cement and asphalt mortar (CA mortar) used in the China Railway Track System (CRTS) I ballastless slab track may encounter a coupling fatigue effect under the high-frequency vibration, load and high-and-low temperature cycles, and the deterioration under fatigue may happen during service of the high-speed railway. In this study, the performance degradation and its mechanism of the CA mortar with and without polymer emulsion incorporated under the coupling fatigue effects of the high-frequency vibration, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…By the end of 2020, the total mileage of the Chinese HSR exceeded 35,000 km [ 1 ]. With this rapid development of HSR, damage problems and structural drawbacks [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] have been observed in many high-speed lines. During the service period, HSR ballastless slab tracks are not only affected by traffic load or foundation deformation, but also by environmental thermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of 2020, the total mileage of the Chinese HSR exceeded 35,000 km [ 1 ]. With this rapid development of HSR, damage problems and structural drawbacks [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] have been observed in many high-speed lines. During the service period, HSR ballastless slab tracks are not only affected by traffic load or foundation deformation, but also by environmental thermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most significant factors producing interfacial cracks [16] and longitudinal buckling [17] in ballastless tracks, the temperature distribution has a great influence on the thermal behavior of ballastless tracks [18][19][20][21][22]. The main causes of the structural diseases in ballastless track structures are the variation of the ambient temperature and the difference in thermal behavior between the cement emulsified asphalt mortar (the CA mortar) and the concrete [23][24][25]. In recent years, research on the temperature distribution in CRTS-II ballastless tracks has increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, under a long-term complex environment and complex loads, the track structure will inevitably experience damage and aging problems, which endanger the driving safety and comfort. Field investigations have shown that structural diseases such as the cracking of the track bed, the cracking of the track slab and interlayer interface cracks (among which interlayer interface cracks between the track slab and the CA mortar are the most common) have appeared on the ballastless slab track operating line [4][5][6][7]. The longitudinal continuous structure characteristics of the CRTS-II slab ballastless track make the structure very sensitive to the temperature effect.…”
Section: Introductionmentioning
confidence: 99%